Rheology, fatty acid profile and quality characteristics of nutrient enriched pizza base - Gupta, Chaitali Sen (J Food Sci Technol, 2014)
Enrichment of thick bread type pizza base (PZB) was done by substituting wheat flour (WF) with 5, 10 and 15 % soya protein isolate (SPI). The rheological characteristics of WF showed that water absorption increased, extensibility and peak viscosity decreased when level of SPI increased from 5 to 15 %. Baking studies showed that spread ratio decreased and hardness values of PZB increased with the increase in amount of SPI from 5 to15 %. Beyond 10 % SPI, the overall quality of PZB was adversely affected. To the optimal blend of 10 % SPI, 5 % psyllium husk (PH) was added and the hydrogenated fat was replaced by canola oil (CAN) in enriched PZB. The enriched PZB treated with combination of additives had 1.7 and 1.6 times more protein and dietary fiber than the control PZB. Fatty acid analysis showed that the enriched PZB had 58.65 % oleic, 6.58 % linolenic acid and 31.28 % polyunsaturated fatty acid and no Trans fat was present.